Methods for Squalene Concentration from Palm Fatty Acid Distillate - Chua, Camilla Soo Leng (2007)
Two methods for separating and concentrating of squalene from palm fatty acid distillate (PFAD) by optimizing the enzymatic hydrolysis of PFAD which has been neutralized-hydrolyzed-neutralized before being run onto adsorption column chromatography and by selection of various adsorbents used in adsorption column were being compared. Extraneous matters, especially free fatty acids (83.8%) and aclyglycerols (12.7%) in the PFAD were first neutralized and removed before being subjected to hydrolysis using commercially available immobilized Candida antarctica lipase at 65°C for 8 h. Neutralization followed by hydrolysis and repetition of neutralization again successfully concentrated squalene from an initial amount of 3.76% to 27.5%. Oil extracted from neutralized-hydrolyzed-neutralized PFAD (NHNPFAD) was then passed through reverse-phase adsorption chromatography using Diaion HP-20®. Squalene was desorbed by hexane, with a recovery of 93%. Factors affecting the enzymatic hydrolysis and squalene concentration of extracted fraction from NHNPFAD were optimized using response surface methodology (RSM). A central composite design was employed to study the responses, namely percentage of squalene concentration (Y1), while reaction time (X1), water content (X2) and enzyme concentration (X3) were the independent variables. Results showed that the regression models generated adequately explained the data variation and significantly (P < 0.05) represented the actual relationships between the reaction parameters and the response. The optimum reaction parameters for maximum yield in squalene concentrations was carried out with 7.05 h, water content, 61.4% (w/w) and enzyme concentration, 2.23% (w/w). Laboratory investigations of squalene adsorption on polyaromatic adsorbents; Diaion HP-20®, Amberlite XAD-1180®, Duolite XAD-761®, SP825®, Dowex Optipore L-285® (DO), SP207® (Sepabeads) and Florisil® were compared for the concentration and recovery of squalene. It was found that the Diaion HP-20® gave the highest concentration of squalene, 27.9% with the recovery of >90%, in comparison with that of Amberlite XAD-1180®, DO L-285®, SP207®, Florisil®, while Duolite XAD-761® is much lower. In terms of squalene concentration and recovery, SP825® is as adsorptive as Diaion HP-20, but nevertheless Diaion HP-20 was chosen as the best adsorbent due to its economical price. Equilibrium parameters for squalene adsorption onto Diaion HP-20® were estimated by linear least square and a trial and error procedure of non-linear method using Langmuir, Freundlich and Redlich-Peterson isotherms. A comparison between linear and non-linear method of estimating the isotherm was reported. The best fitting isotherm was Freundlich isotherm in linear method and Langmuir and Redlich - Peterson isotherm equation in the non-linear method. The results show that both linear and non-linear method could be use to obtain the parameters with high coefficient of determination (R2>0.90). Redlich-Peterson isotherm is a special case of Langmuir isotherm when the Redlich-Peterson isotherm constant g was unity.